Population Modeling Approach to Optimize Crop Harvest Strategy. The Case of Field Tomato - Tran, Dinh T.; Hertog, Maarten L. A. T. M.; Tran, Thi L. H.; Quyen, Nguyen T.; Van de Poel, Bram; Mata, Clara I.; Nicolaï, Bart M. (Frontiers in Plant Science, 2017)
In this study, the aim is to develop a population model based approach to optimise fruit harvesting strategies with regard to fruit quality and its derived economic value. This approach was applied to the case of tomato fruit harvesting under Vietnamese conditions. Fruit growth and development of tomato (cv. ‘Savior’) was monitored in terms of fruit size and colour during both the Vietnamese winter and summer growing seasons. A kinetic tomato fruit growth model was applied to quantify biological fruit-to-fruit variation in terms of their physiological maturation. This model was successfully calibrated. Finally, the model was extended to translate the fruit-to-fruit variation at harvest into the economic value of the harvested crop. It can be concluded that a model based approach to the optimization of harvest date and harvest frequency with regard to economic value of the crop as such is feasible. This approach allows growers to optimize their harvesting strategy by harvesting the crop at more uniform maturity stages meeting the stringent retail demands for homogeneous high quality product. The total farm profit would still depend on the impact a change in harvesting strategy might have on related expenditures. This model based harvest optimisation approach can be easily transferred to other fruit and vegetable crops improving homogeneity of the postharvest product streams.